Ketamine suppresses the ventral striatal response to reward anticipation: a cross-species translational neuroimaging study - Francois, Jennifer; Meyer-Lindenberg, Andreas (Neuropsychopharmacology, 2016)
Convergent evidence implicates regional neural responses to reward anticipation in the pathogenesis of several psychiatric disorders, such as schizophrenia, where blunted ventral striatal responses to positive reward are observed in patients and at-risk populations. In vivo oxygen amperometry measurements in the ventral striatum in awake, behaving rats reveal reward-related tissue oxygen changes that closely parallel blood oxygen level dependent (BOLD) signal changes observed in human functional magnetic resonance imaging (fMRI), suggesting that a cross-species approach targeting this mechanism might be feasible in psychopharmacology. The present study explored modulatory effects of acute, subanaesthetic doses of ketamine - a pharmacological model widely used in psychopharmacological research, both preclinically and clinically - on ventral striatum activity during performance of a reward anticipation task in both species, using fMRI in humans and in vivo oxygen amperometry in rats. In a region-of-interest analysis conducted following a cross-over placebo and ketamine study in human subjects, an attenuated ventral striatal response during reward anticipation was observed following ketamine relative to placebo during performance of a monetary incentive delay task. In rats, a comparable attenuation of ventral striatal signal was found after ketamine challenge, relative to vehicle, in response to a conditioned stimulus that predicted delivery of reward. This study provides the first data in both species demonstrating an attenuating effect of acute ketamine on reward-related ventral striatal (O2) and fMRI signals. These findings may help elucidate a deeper mechanistic understanding of the potential role of ketamine as a model for psychosis, show that cross-species pharmacological experiments targeting reward signaling are feasible, and suggest this phenotype as a promising translational biomarker for the development of novel compounds, assessment of disease status, and treatment efficacy.
Gesehen am 04.04.2019
Published online 21 October 2015